Novel injectable calcium phosphate scaffold with human periodontal ligament stem cell encapsulation in microbeads for bone regeneration - Qiu, Gengtao; Huang, Mingguang; Ke, Difeng; Liu, Jin; Weir, Michael D.; Ma, Tao; Wang, Ping; Oates, Thomas W.; Schneider, Abraham; Xia, Yang; Xu, Hockin H. K.; Zhao, Liang (Frontiers in Materials, 2022)
Objectives: 1) Develop a novel construct of human periodontal ligament stem cells (hPDLSCs) encapsulated in degradable alginate microbeads (DAMB) with human platelet lysate (hPL) and injectable calcium phosphate cement (ICPC); 2) Investigate the proliferation and osteogenic differentiation of hPDLSCs in ICPC with hPL as a xeno-free supplement and animal serum replacement for bone tissue engineering applications. Methods: hPDLSCs were encapsulated in alginate-fibrin microbeads (DAMB + fibrin), alginate-hPL degradable microbeads (DAMB + hPL), or alginate-fibrin-hPL microbeads (DAMB + fibrin + hPL). The proliferation and osteogenic differentiation of hPDLSCs were investigated in culturing with the ICPC scaffold. Results: Flexural strength of ICPC was 8.4 ± 0.91 MPa, and elastic modulus was 1.56 ± 0.1 GPa, exceeding those of cancellous bone. hPDLSCs had higher viability in DAMB + fibrin + hPL group than in DAMB + fibrin. ALP was 69.97 ± 16.96 mU/mg for ICPC + DAMB + fibrin + hPL group, higher than 30.68 ± 2.86 mU/mg of ICPC + DAMB + fibrin (p < 0.05) and 4.12 ± 1.65 mU/mg of control (p < 0.01). At 7 days, osteogenic gene expressions (ALP, RUNX2, COL1, and OPN) in ICPC + DAMB + fibrin + hPL and ICPC + DAMB + fibrin were 4–11 folds that of control. At 21 days, the hPDLSC-synthesized bone mineral amounts in ICPC + DAMB + fibrin + hPL and ICPC + DAMB + fibrin were 13.2 folds and 11.1 folds that of control group, respectively. Conclusion: The novel injectable CPC scaffold encapsulating hPDLSCs and hPL is promising to protect and deliver hPDLSCs. The hPL-based medium significantly enhanced the osteogenic differentiation of hPDLSCs in ICPC + DAMB + fibrin + hPL construct, suggesting a promising xeno-free approach for bone tissue regeneration applications.